Etika Komunikasi Islami dalam Menghadapi Hoaks dan Disinformasi di Era Digital - Faisal Faisal (Yayasan Nanggroe Aceh Mulia, 2025)
The development of digital technology has accelerated the production and exchange of information while simultaneously increasing the circulation of hoaxes and disinformation within society. The ease of sharing messages without adequate verification may generate misunderstanding, social polarization, reputational damage, and declining public trust. Previous studies have extensively discussed digital literacy, fact-checking, platform regulation, and technological detection of false information. However, relatively few studies have integrated these approaches with the moral responsibility of communicators grounded in Islamic communication principles. This study aims to analyze the principles of Islamic communication ethics and formulate an applicable framework for receiving, verifying, interpreting, and disseminating digital information. It employed library research using a qualitative-descriptive approach. The data were obtained from Islamic normative sources, books, journal articles, research reports, and institutional documents addressing Islamic communication, digital literacy, social media, hoaxes, and disinformation. The data were examined through content and thematic analyses involving literature selection, coding, thematic categorization, source comparison, interpretation, and conceptual synthesis. The findings demonstrate that hoaxes and disinformation emerge from the interaction of technological speed, inadequate verification, emotional impulses, communicators’ interests, and weak user responsibility. Proper intention, tabayyun, qaulan sadidan, trustworthiness, justice, civility, and public benefit constitute relevant Islamic ethical foundations for addressing these challenges. This study proposes an Islamic digital communication model comprising intention orientation, truth verification, benefit evaluation, ethical delivery, and corrective responsibility. It concludes that efforts to address hoaxes become more comprehensive when digital literacy and fact-checking abilities are combined with ethical and religious awareness. The contribution of this research lies in transforming Islamic communication principles from general normative teachings into an operational framework applicable to education, Islamic preaching, journalism, institutional communication, and everyday digital media practices. This framework also positions every media user as a moral subject who is accountable for the accuracy, purpose, method, and consequences of disseminated information.